2018
DOI: 10.5194/os-14-293-2018
|View full text |Cite
|
Sign up to set email alerts
|

Short commentary on marine productivity at Arctic shelf breaks: upwelling, advection and vertical mixing

Abstract: Abstract. The future of Arctic marine ecosystems has received increasing attention in recent years as the extent of the sea ice cover is dwindling. Although the Pacific and Atlantic inflows both import huge quantities of nutrients and plankton, they feed into the Arctic Ocean in quite diverse regions. The strongly stratified Pacific sector has a historically heavy ice cover, a shallow shelf and dominant upwelling-favourable winds, while the Atlantic sector is weakly stratified, with a dynamic ice edge and a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…We have not found any indications to that effect during our sampling campaigns. For a more detailed description of the issue of wind-driven upwelling in Arctic shelfbreak areas, see Randelhoff and Sundfjord (2018). All else aside, even actual upwelling in winter would not enhance productivity in our study area since, as we have shown, the surface mixed layer is already replete by that time and well before the onset of the next spring bloom.…”
Section: Thermal Convection In Wintermentioning
confidence: 81%
“…We have not found any indications to that effect during our sampling campaigns. For a more detailed description of the issue of wind-driven upwelling in Arctic shelfbreak areas, see Randelhoff and Sundfjord (2018). All else aside, even actual upwelling in winter would not enhance productivity in our study area since, as we have shown, the surface mixed layer is already replete by that time and well before the onset of the next spring bloom.…”
Section: Thermal Convection In Wintermentioning
confidence: 81%
“…The shelf north of Svalbard is 150–200 m deep versus 50–60 m in the Beaufort Sea where upwelling is particularly common. The much greater depth north of Svalbard implies that shelf break upwelling is not likely to be important here; the outer shelf is too deep for the surface and Ekman layers to overlap and interact (see Randelhoff & Sundfjord, ). In addition, the wind field is highly variable both in strength and direction with only few short periods of easterly (i.e., upwelling favorable) winds lasting several consecutive days (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…After an initial look into heat exchange at the ocean‐atmosphere interface, we investigate the role of vertical fluxes in the water column as deduced from current shear variance as well as the influence of tides. While wind‐driven upwelling is a well‐documented process in parts of the Canadian Arctic (e.g., Pickart et al, ), the shelf geometry north of Svalbard is not favorable for shelf break upwelling driven by along‐slope winds (Randelhoff & Sundfjord, ). We show, however, that Ekman pumping can lead to instances with considerable isopycnal uplift.…”
Section: Resultsmentioning
confidence: 99%
“…Nutrient supply from AW and BSW to the overlying PSW occurs by autumn and winter mixing, upwelling along the shelf break and Polar Front, tidal forcing and episodic windmixing in spring/summer [31,37,[49][50][51]. Recent evidence from the shelf-slope north and west of Svalbard shows that thermally induced convective mixing [52] is more important than wintertime shelf-break upwelling in the AW inflow region [53]. Atlantification-the increasing advection of warm (greater than 0°C), saline, nutrient-rich AW at intermediate depth (150-900 m)-is occurring along the continental slope north of Svalbard and over the Barents shelf from the south [24,[54][55][56][57].…”
Section: (B) the Barents Seamentioning
confidence: 99%